A switch in regulatory T cells through farm exposure during immune maturation in childhood. Issue 4 (17th November 2016) - Schröder, P. C.; Illi, S.; Casaca, V. I.; Lluis, A.; Böck, A.; Roduit, C.; Depner, M.; Frei, R.; Genuneit, J.; Pfefferle, P. I.; Roponen, M.; Weber, J.; et al.
Abstract: Background: Farm exposure protects against development of allergies early in life. At 4.5 years, protection against asthma by farm‐milk exposure was partially mediated by regulatory T cells (Tregs). The aim of this study was to investigate the critical time window of the 'asthma‐protective' farm effect via Tregs during childhood immune maturation. Methods: Tregs were assessed longitudinally at 4.5 and 6 years in 111 children (56 farm and 55 reference children) from the PASTURE/EFRAIM birth cohort (flow cytometry). Peripheral blood mononuclear cells were cultured unstimulated (U), with phorbol 12‐myristate 13‐acetate/ionomycin (PI) or lipopolysaccharide (LPS), and stained for Tregs (CD4 + CD25 high FOXP3 upper20% ). mRNA expression of Treg/Th1/Th2/Th17‐associated cell markers was measured ex vivo . Suppressive capacity of Tregs on effector cells and cytokines was assessed. Detailed questionnaires assessing farm exposures and clinical phenotypes from birth until age 6 years were answered by the parents. Results: Treg percentage before and after stimulation and FOXP3 mRNA expression ex vivo decreased from age 4.5 to 6 years ( P (U, LPS) < 0.001; P (PI) = 0.051; P ( FOXP3 ) < 0.001). High vs low farm‐milk and animal‐stable exposure was associated with decreased LPS‐stimulated Treg percentage at age 6 years ( P (LPS) = 0.045). Elevated LPS‐stimulated‐Treg percentage at age 6 was associated with increased risk of asthma (aOR = 11.29, CI: 0.96–132.28, P = 0.053). Tregs from asthmatics vs nonasthmatics suppressed IFN‐γ ( P = 0.015) and IL‐9 ( P = 0.023) less efficiently. mRNA expression of Th1/Th2/Th17‐associated cell markers decreased between 4.5 and 6 years ( P < 0.001). Conclusions: Tregs at the age of 6 years were decreased with farm exposure and increased within asthmatics, opposite to age 4.5 years. This immunological switch defines a critical 'time window' for Treg‐mediated asthma protection via environmental exposure before age 6 years.